Pengaruh Kualitas Produk Digital Banking Terhadap Kepuasan Nasabah Bank Nagari Cabang Utama Padang - Maulana, Fadjri; Embun Sari, Puti (LPPM Universitas Dharma Andalas, 2025)
This study aims to determine the effect of website design quality, website information quality, punctuality, trust, and security on Customer Satisfaction at Bank Nagari Main Branch Padang. The population in this study were all users of Bank Nagari Main Branch Digital Banking Products. This study uses a quantitative approach with sampling using the non-probability sampling method. The analysis tool uses multiple linear regression analysis. Analysis of the data used is Statistical Product and service solutions (SPSS).The results of the research by testing the hypothesis show that the variables of website design quality, website information quality, punctuality, trust, and security simultaneously affect customer satisfaction with digital banking users at Bank Nagari Main Branch. Partially, the variables of website design quality, website information quality, punctuality, trust, and security have a significant effect on customer satisfaction with digital banking users at Bank Nagari, Padang Main Branch.